The Health Services Legal Problems of In Vitro Fertilization (IVF) Program Patients in Indonesia - Edi As'adi; Norma Sari (Universitas Ahmad Dahlan, 2021)
Introduction to The Problem: Every married couple expects children that the Constitution guarantees. However, the difficulty of having a child tends to be a problem in maintaining married life. Some couples decide to have a child by undergoing In Vitro Fertilization (IVF) Program. The arising problems are on how the current regulation of the IVF program and how to fulfil the rights of IVF program patients from consumer protection law.Purpose/Objective Study: This article focus on the problem of health services for IVF program patients based on the values of justice on the ground of consumer protection law in Indonesia.Design/Methodology/Approach: This study is socio-legal research. However, to support the validity of research, an empirical approach is critical to do-furthermore, where data obtained through interviews based on the researcher’s own experience.Findings: IVF program agreement between the IVF clinic and patients is a law based on Article 1338 of the Indonesian Civil Code. Even so, the research validation was still carried out with the support of an empirical approach. The results of this research are that the current IVF program has not been able to protect its patients’ rights. Patients’ position tends to be weak compared to the clinic or IVF hospital; the concept of the IVF program implementation agreement does not protect patient rights. In the future, attempts to protect IVF patients’ rights need an integrated and comprehensive regulation from the philosophical, juridical, and sociological basis to its practical implementation.